Obesity enriches for tumor protective microbial metabolites and treatment refractory cells to confer therapy resistance in PDAC. (31st December 2022) - Kesh, Kousik; Mendez, Roberto; Mateo-Victoriano, Beatriz; Garrido, Vanessa T; Durden, Brittany; Gupta, Vineet K; Oliveras Reyes, Alfredo; Merchant, Nipun; Datta, Jashodeep; Banerjee, Santanu; Banerjee, Sulagna
ABSTRACT: Obesity causes chronic inflammation and changes in gut microbiome. However, how this contributes to poor survival and therapy resistance in patients with pancreatic cancer remain undetermined. Our current study shows that high fat diet-fed obese pancreatic tumor bearing mice do not respond to standard of care therapy with gemcitabine and paclitaxel when compared to corresponding control diet-fed mice. C57BL6 mice were put on control and high fat diet for 1 month following with pancreatic tumors were implanted in both groups. Microbiome of lean (control) and obese (high fat diet fed) mice was analyzed. Fecal matter transplant from control mice to obese mice sensitized tumors to chemotherapy and demonstrated extensive cell death. Analysis of gut microbiome showed an enrichment of queuosine (Q) producing bacteria in obese mice and an enrichment of S-adenosyl methionine (SAM) producing bacteria in control diet-fed mice. Further, supplementation of obese animals with SAM sensitized pancreatic tumors to chemotherapy. Treatment of pancreatic cancer cells with Q increased PRDX1 involved in oxidative stress protection. In parallel, tumors in obese mice showed increase in CD133 + treatment refractory tumor populations compared to control animals. These observations indicated that microbial metabolite Q accumulation in high fat diet-fed mice protected tumors from chemotherapy induced oxidative stress by upregulating PRDX1. This protection could be reversed by treatment with SAM. We conclude that relative concentration of SAM and queuosine in fecal samples of pancreatic cancer patients can be developed as a potential biomarker and therapeutic target in chemotherapy refractory pancreatic cancer.